The harmony of the interpretation of rights in the democratic constitution of political theory and legal theory - Lortanapaisan, Tanaroj (Thai Social Science Journal, 2025)
The article ,the harmony of the interpretation of rights in the democratic constitution of political theory and legal theory ,makes the argument that various political and legal theories’ readings of constitutional rights can coincide because both ideologies aim to establish a contemporary state that protects individual liberty. This may be compatible Although nowadays both theories seem to be used in ways that produce different results. Both views agree that the legal interpretation of rights must connect to the justice and validity of the foundation of constitutional rights, in which the people have the last say. The legal interpretation of the constitution must be consistent with both legal and political justice, and the political idea of justice in equal participation in self–determination must take into account. The people who make laws through that are the moral junction of both legal and political theory, and which links the process of establishing legal and political rights because the true law depends on the foundation of social legitimacy.